Swifterbant stones : the Neolithic stone and flint industry at Swifterbant (the Netherlands): from stone typology and flint technology to site function - Devriendt, I. (Izabel Ivan Jeanne Alain Lieve Marita), 1976- (Groningen archaeological studies ;, 2014)
Annotation